RESPON KACANG HIJAU (VIGNA RADIATA L.) VARIETAS KUTILANG DAN VIMA 2 TERHADAP JENIS PUPUK ORGANIK - Nome, Erton; Sutoyo, Sutoyo; Marwoto, Marwoto (Universitas Tribhuwana Tunggadewi, 2019)
The Efforts to maintain and increase the production of green beans, in the aspect of crop cultivation requires the use of organic fertilizers and superior varieties. This research aims to study the response of mung bean varieties to the use of organic fertilizer. This research was conducted in Tlogomas, Lowokwaru District, Malang City, East Java Province, from April 2019 to June 2019. Experiments using the RAK nested consisting of 2 factors, factor 1, finches and vima 2 varieties, factor 2 types of petroganic organic fertilizer, compost, cow dung and bioogene. The results showed that the use of organic fertilizers affected plant height, number of leaves, number of branches and age of flowering, but did not significantly affect the number of pods per plant, pod length, seed dry weight per plant and 100 seed dry weight. Variety of combination with the type of organic fertilizer affects plant height, number of leaves, number of branches, but does not significantly affect flowering age, number of pods per plant, pod length, seed dry weight per plant and 100 seed dry weight. Plant height finches variety combined types of fertilizer manure 41,28 cm, the number of leaves of finches variety combination type of compost fertilizer 20,00 strands, the number of branches of finches variety combination type of compost fertilizer 4,78, the number of pods finite variety finches combination type of compost fertilizer 8,33, the length of the vima variety 2 pods combination of 8,60 cm petroganic fertilizer, the number of seeds per pod of the vima variety 2 compost type 8,84 compost, the dry weight of the variety finches variety of biogreen fertilizer 3,47 g, the weight of 100 seeds of the finches variety combination biogreen fertilizer 7,01 g. Upaya mempertahankan dan meningkatkan produksi kacang hijau, dalam aspek budidaya tanaman diperlukan penggunaan pupuk organik dan varietas unggul. Penelitian ini bertujuan untuk mempelajari respon varietas kacang hijau terhadap penggunaan jenis pupuk organik. Penelitian ini dilaksanakan di Tlogomas, Kecamatan Lowokwaru, Kota Malang, Provinsi Jawa Timur, mulai April 2019 sampai Juni 2019. Percobaan menggunakan RAK tersarang yang terdiri dari 2 faktor, faktor 1 varietas kutilang dan vima 2, faktor 2 jenis pupuk organik petroganik, kompos, kotoran sapi dan bioogren. Hasil penelitian menunjukkan Penggunaan jenis pupuk organik berpengaruh terhadap tinggi tanaman, jumlah daun, jumlah cabang, dan umur berbunga, Namun tidak berpengaruh nyata terhadap jumlah polong per tanaman, panjang polong, berat kering biji per tanaman dan berat kering 100 biji. Varietas kombinasi dengan jenis pupuk organik berpengaruh terhadap tinggi tanaman, jumlah daun, jumlah cabang, Namun tidak berpengaruh nyata terhadap umur berbunga, jumlah polong per tanaman, panjang polong, berat kering biji per tanaman dan berat kering 100 biji. Tinggi tanaman varietas kutilang kombinasi jenis pupuk kotoran sapi 41,28 cm, jumlah daun varietas kutilang kombinasi jenis pupuk kompos 20,00 helai, jumlah cabang varietas kutilang kombinasi jenis pupuk kompos 4,78, jumlah polong varietas kutilang kombinasi jenis pupuk kompos 8,33, panjang polong varietas vima 2 kombinasi jenis pupuk petroganik 8,60 cm, jumlah biji per polong varietas vima 2 kombinasi jenis pupuk kompos 8,84, berat kering varietas kutilang kombinasi jenis pupuk biogreen 3,47 g, berat 100 biji varietas kutilang kombinasi jenis pupuk biogreen 7,01 g.